Loneliness in University Students during Two Transitions: A Mixed Methods Approach Including Biographical Mapping - Jaud, Janna; Görig, Tatiana; Konkel, Tobias; Diehl, Katharina (International Journal of Environmental Research and Public Health, 2023)
Several studies have shown that loneliness is prevalent in university students. However, up to now, it is less clear how transitions during this life stage are associated with loneliness. Therefore, we aimed to explore the association of loneliness with the transition from high school to university and the transition into the COVID-19 pandemic. Twenty students were interviewed in qualitative interviews based on a semi-structured guide that also included biographical mapping. In addition, the participants reported social and emotional loneliness based on the six-item De Jong Gierveld Loneliness Scale for three points in time: (1) at the time of the interview, (2) at the beginning of their studies at the university and (3) at the start of the COVID-19 pandemic. The qualitative data were analyzed using a structuring content analysis following Mayring. The quantitative data were analyzed using descriptive statistics. We found that emotional loneliness increased both during high school graduation and at the start of study at the university, as well as at the beginning of the COVID-19 pandemic. Social loneliness was higher during university studies than during the last years at high school and increased at the beginning of the pandemic. The results indicate that both transitions played an important role for perceived social and emotional loneliness. Further quantitative studies in larger samples will be relevant in the future to better target the responses to loneliness during transitions. Universities can actively counteract loneliness, especially during the transition from high school to university, by organizing events and meeting places where new students can network.
CRIS-Team Scopus Importer:2023-03-10
Keywords: COVID-19; loneliness; students; transition; university